EVALUASI IMPLEMENTASI KEBIJAKAN PENDIDIKAN GRATIS DI KABUPATEN PASAMAN - Siti Asyiah; M. Fachri Adnan; Adil Mubarak (Department of Public Administration, Universitas Negeri Surabaya, 2018)
The Regulation of Pasaman number 2 Year 2013 set about free education in Pasaman. However, in the time after the implementation of the free education in Pasaman found several problems that do not comply with the policy direction of free education, such as the discovery of some schools are asking for charges to parents/students for salary of contract teachers. This research was to evaluate the implementation of free education regulations in Pasaman and to evaluate the results of the implementation of free education regulation in Pasaman. The determination of sample is using purposive sampling technique . Research conducted at the Department of education and culture of Pasaman, SMAN 1 of Lubuk Sikaping, SMAN 1 Panti, SMPN of 1 Panti and SDN 09 Petok. This Research using qualitative approach and descriptive method. The results showed that the implementation of regulation of free education in Pasaman is not good enough, it can be seen from the communication is less effective to policy target, available resources are already quite optimal for carrying out the policy, although there are still deficiencies in budgetary resources for the development of schools and students, the tance of implementor is quite well, however, there are schools that asked for the charges, and in the bureaucratic structure is quite simple but does not have a clear SOP . the result of the implementation of free education regulation objectives already achieved with optimal use of funds and human resources for the implementation of the policy, the policy of free education enough to satisfy the communitys needs in education, the implementation of the free education already evenly, the community of Pasaman supports the implementation of free education regulation , the implementation of the free education is right to implemented in Pasaman.